2005
DOI: 10.1128/aem.71.9.5544-5550.2005
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Community Analysis by Large-Scale Sequencing of Environmental Samples

Abstract: Fungi are an important and diverse component of soil communities, but these communities have proven difficult to study in conventional biotic surveys. We evaluated soil fungal diversity at two sites in a temperate forest using direct isolation of small-subunit and internal transcribed spacer (ITS) rRNA genes by PCR and high-throughput sequencing of cloned fragments. We identified 412 sequence types from 863 fungal ITS sequences, as well as 112 ITS sequences from other eukaryotic microorganisms. Equal proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
564
5
31

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 823 publications
(634 citation statements)
references
References 42 publications
(39 reference statements)
34
564
5
31
Order By: Relevance
“…The abundance of Ascomycota was much higher than in previous reports (O'Brien et al 2005). By further analysis at the genus level, 51 abundant genera (more than 1 % of total sequences) were found in rhizosphere soils and 27 in roots (Tables S1 & S2), but the genera Fusarium and Cylindrocarpon, which were considered to be the main pathogens causing root-rot of P. notoginseng (Mao et al 2014), showed no significant difference between diseased and healthy plants both in rhizosphere soils and in roots.…”
Section: Discussioncontrasting
confidence: 74%
“…The abundance of Ascomycota was much higher than in previous reports (O'Brien et al 2005). By further analysis at the genus level, 51 abundant genera (more than 1 % of total sequences) were found in rhizosphere soils and 27 in roots (Tables S1 & S2), but the genera Fusarium and Cylindrocarpon, which were considered to be the main pathogens causing root-rot of P. notoginseng (Mao et al 2014), showed no significant difference between diseased and healthy plants both in rhizosphere soils and in roots.…”
Section: Discussioncontrasting
confidence: 74%
“…A value of 97% ITS identity was used as a DNA barcoding criterion (O’Brien et al 2005). Sequence-based identifications were made by searching with Blastn in the UNITE+INSD database of fungal nucleotide sequences (Abarenkov et al 2010; Tedersoo et al 2014)…”
Section: Methodsmentioning
confidence: 99%
“…The uncultured ascomycete relative of this Massarina sp., strain CNT-016, was the only one identified from a terrestrial soil habitat (O'Brien et al, 2005); the other strains in this clade were isolated from plant material (Aptroot, 1998) collected from locations including Europe, North America, Asia and Papua New Guinea. No secondary metabolites are known from species in the Massarina clade 1 except for the study reported here.…”
Section: Biologymentioning
confidence: 99%